2020
DOI: 10.1002/curj.40
|View full text |Cite
|
Sign up to set email alerts
|

Curricular responses to Computer Science provision in schools: current provision and alternative possibilities

Abstract: This paper explores the rationales underpinning the introduction of Computer Science (CS) into school curricula and examines the ways in which educational systems have responded to these growing calls. In outlining the possible ways that educational systems can respond to this demand, the paper makes use of a conceptual framework through which the various possibilities for the provision of CS in school curricula can be categorised. The paper analyses and discusses possible modes of provision identifying the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This would appear to be at odds with the dominant justification for its inclusion as one would expect that aspects of coding would be integrated across the curriculum given the rhetoric of its relevance for all and the universal transferrable skills it is reported to help develop. The high level of consistency in terms of the content of the subject of Computer Science across different countries (European Schoolnet, 2015; Heintz et al., 2016; McGarr & Johnston, 2020) would suggest it is a highly classified and framed subject. It therefore appears to take on all the characteristics of a traditional school subject at odds with the justifications for its inclusion on the curriculum as an essential skill for all students that has application and relevance across the curriculum.…”
Section: Section 3: Discussion and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This would appear to be at odds with the dominant justification for its inclusion as one would expect that aspects of coding would be integrated across the curriculum given the rhetoric of its relevance for all and the universal transferrable skills it is reported to help develop. The high level of consistency in terms of the content of the subject of Computer Science across different countries (European Schoolnet, 2015; Heintz et al., 2016; McGarr & Johnston, 2020) would suggest it is a highly classified and framed subject. It therefore appears to take on all the characteristics of a traditional school subject at odds with the justifications for its inclusion on the curriculum as an essential skill for all students that has application and relevance across the curriculum.…”
Section: Section 3: Discussion and Implicationsmentioning
confidence: 99%
“…The rationales for the introduction of the study of computers in schools vary from explicit economic rationales concerned about national economic competitiveness (McGarr & Johnston, 2020; Tucker, 2003) to broader social and educational justifications aimed at addressing inequalities of opportunity or developing specific cognitive skills for students such as problem‐solving and analytical skills. These different agendas and rationales could be seen as a product of the messiness of the policy‐making process where multiple stakeholders elbow for influence (Williamson et al., 2019) or a way of ensuring that the arguments for the introduction of the study of computers appeal to the widest possible audience for maximum traction.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the functional view of code and computing dominates in curricula globally (eg, Williamson et al., 2019; Wu et al., 2020). One possible explanation for the paucity of critical approaches is that studies carried out in various countries, including Australia, England, Finland, Ireland and Sweden, have identified that the interests of the technology industry have played a notable role in shaping the way the ‘whys’ and ‘hows’ of computing have been attached to curricula (Bresnihan et al., 2015; McGarr & Johnston, 2020; Mertala et al., 2020; Williamson et al., 2019). Coding skills are claimed to be ‘a success factor for a society’ (Tuomi et al., 2018, p. 419), and the main objective for computing education—alongside supporting students' problem solving and learning skills—appears to be to maximize the potential pool of future coders and tech entrepreneurs (Larke, 2019; Mertala et al., 2020; Williamson, 2017; Williamson et al., 2019).…”
Section: Computing In Curricula: Tensioned Relationship Between Funct...mentioning
confidence: 99%
“…While computing has been (re)introduced into the basic education curricula in various countries (Bresnihan et al, 2015;McGarr & Johnston, 2020;Mertala et al, 2020;Sentance & Csizmadia, 2017;Williamson et al, 2019), its actual implementation appears to be inconsistent. There are schools in which computing education is commonplace (Duncan et al, 2017;Geldreich et al, 2018), while the implementation seems to be lagging behind in others (Larke, 2019;Tanhua-Piiroinen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of Computer Science at Senior Cycle will change the way Irish schools approach computing and information technology [1][2][3][4] -replacing the idea of IT literacy and passive consumers of computing to innovators, creators and designers [4][5][6]. The National Council for Curriculum and Assessment (NCCA) was formed to lead developments in educational curriculum and assessment and to support the implementation of changes resulting from this work.…”
Section: Introductionmentioning
confidence: 99%